Structure and stability of acrolein and allyl alcohol networks on Ag(111) from density functional theory based calculations with dispersion corrections - Ferullo, Ricardo (2013)
The interaction of acrolein and allyl alcohol with the Ag(111) surface has been studied by means of periodic density functional theory based calculations including explicitly dispersion terms. Different coverage values have been explored going from isolated adsorbed molecules to isolated dimers, interacting dimers or ordered overlayers. The inclusion of the dispersion terms largely affects the calculated values of the adsorption energy and also the distance between adsorbed molecule and the metallic surface but much less the adsorbate-adsorbate interactions. Owing to the large dipole moment of acrolein, the present calculations predict that at high coverage this molecule form stable extensive two-dimensional network on the surface, caused by the alignment of the adsorbate dipoles. For the case of allyl alcohol, dimers and complex networks exhibit similar stability.